2017
DOI: 10.3390/ijerph14020204
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Criteria in the Spanish Public Works Procurement Process

Abstract: Green Public Procurement (GPP) is defined as a process of contracting products, services, and works with the least possible damage to the environment during their life cycle. In order to improve the knowledge about GPP, a study of the use of environmental tendering criteria in the Spanish public construction sector has been performed. The results of this study show that the use of environmental criteria in Spanish public sector construction procurement is low in comparison to a certain group of countries, know… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
46
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(55 citation statements)
references
References 45 publications
7
46
1
1
Order By: Relevance
“…Which is the impact of the procedures related with the GPP? ), many studies have analysed the governmental procedures regarding the integration of the environmental criteria in the public offers of purchase (Oruezabala and Rico, 2012;Pacheco-Blanco and Bastante-Ceca, 2016;Varnäs et al, 2009;Nissinen et al, 2009;Faith-Ell, 2005;Fet et al, 2011;Testa et al, 2016a;Lundberg et al, 2016;Michelsen and de Boer, 2009), the level of use of these criteria in different countries (Nissinen et al, 2009;Fuentes-Bargues et al, 2017), the factors that influence the inclusion of the green criteria in the public auctions (Testa et al, 2012), the effects of including environmental criteria in the offers of purchase (Parikka-Alhola, 2008). The contracting authorities must award a contract based on the most economically advantageous offer (by applying the criteria: price, cost, quality-price ratio, quality-cost ratio).…”
Section: Table No 3: Citations Per Yearmentioning
confidence: 99%
See 2 more Smart Citations
“…Which is the impact of the procedures related with the GPP? ), many studies have analysed the governmental procedures regarding the integration of the environmental criteria in the public offers of purchase (Oruezabala and Rico, 2012;Pacheco-Blanco and Bastante-Ceca, 2016;Varnäs et al, 2009;Nissinen et al, 2009;Faith-Ell, 2005;Fet et al, 2011;Testa et al, 2016a;Lundberg et al, 2016;Michelsen and de Boer, 2009), the level of use of these criteria in different countries (Nissinen et al, 2009;Fuentes-Bargues et al, 2017), the factors that influence the inclusion of the green criteria in the public auctions (Testa et al, 2012), the effects of including environmental criteria in the offers of purchase (Parikka-Alhola, 2008). The contracting authorities must award a contract based on the most economically advantageous offer (by applying the criteria: price, cost, quality-price ratio, quality-cost ratio).…”
Section: Table No 3: Citations Per Yearmentioning
confidence: 99%
“…Numerous difficulties related to the GPP were highlighted in the analysed studies. Among them, we mention the lack of clarity of the environmental criteria (Michelsen and de Boer, 2009;Testa et al, 2012;Nissinen et al, 2009), the existence of too generic criteria, which prevents the easy verification by the contracting authority for their compliance (Fuentes-Bargues et al, 2017), the poor presence of environmental criteria in the evaluation of tenders, rarely affecting the awarding decisions (Varnäs et al, 2009;Fuentes-Bargues et al, 2018 ), including them mainly as technical specifications (Testa et al, 2016b). The use of environmental criteria is encountered in the case of national administrations to a greater extent, because they have more resources and better training of personnel on environmental issues (Fuentes-Bargues et al, 2017).…”
Section: Table No 3: Citations Per Yearmentioning
confidence: 99%
See 1 more Smart Citation
“…Green procurement, which is part of Sustainable Public Procurement Program under the United Nations Environment Program [63], surfaced as a sub-theme during the pilot coding. While this suggested the presence of green procurement as a hypothesized upstream intervention mechanism, studies have shown supply chain and knowledge gaps in operationalizing this and thus mixed results of this emerging phenomenon [86][87][88]. Further in-depth studies of green procurement could be conducted to deepen the understanding and application, particularly in Asia.…”
Section: Added Theoretical Constructsmentioning
confidence: 99%
“…To date extant literature indicates a limited exploration in the context of the public sector [9], [13], [18], with the great majority of these studies being carried out in private companies [19]- [22]. Furthermore, there is a preponderance of works conducted in developed countries such as Sweden [23], UK [16], [24][25][26], Spain [3], [27], The Netherlands [7], [28], USA [18], [29], Australia [30], Norway [1], Denmark [31], Germany [32] and Canada [33], while SPP surveys within the context of developing and underdeveloped countries have been systematically neglected [34]. Whereas achieving a sustainable level of consumption and production 'requires a diversified approach in developed and developing economies' [35] since their intrinsic characteristics vary in relation to their consumption patterns, economic condition, industrialization level, demography and socio-cultural factors [34], [36], this research fills this gap through a study in Brazil, a developing country and the largest economy in Latin America.…”
Section: Introductionmentioning
confidence: 99%